Customer Experience Pengguna Brimo dalam Membangun Loyalitas Nasabah Generasi Z: Studi Kualitatif pada PT Bank Rakyat Indonesia (Persero) Tbk. Kantor Cabang Pembantu Nginden Semolo Surabaya - Faserin Sahnia; Silvi Silvi; Sundari Putri Langit Kemul Mega; Ida Ayu Nuh Kartini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid digital transformation of Indonesian banking has intensified competition for Generation Z customers. This qualitative case study explores how customer experience with BRImo, a mobile banking application of PT Bank Rakyat Indonesia, shapes Generation Z customer loyalty at a sub-branch office in Surabaya. Two informants were selected through purposive sampling: a Customer Service officer (I1) and a Generation Z user (I2). Data were collected through in-depth interviews, non-participant observation, and documentation, then analyzed using the Miles, Huberman, and Saldana model. Thematic analysis identified five themes: ease of access and feature completeness as the gateway to positive experience; lifesaver experience during critical moments as a driver of emotional loyalty; the role of customer service as a human touchpoint and digital navigator; security perceived as a baseline requirement rather than a differentiator; and digital ecosystem embeddedness as a loyalty lock-in mechanism. These findings extend the understanding of customer experience in Indonesian mobile banking and offer practical implications for digital banking retention strategies targeting young customers.